Dog’s ownership. Benefits for the psycho-emotional health of middle-aged patients with Type 2 Diabetes Mellitus - Hugues Hernandorena, Beatriz (2018)
The possession of companion dogs has a positive effect on the prevention and recovery of mental health in people. Patients with diabetes mellitus type 2 (DM2) of middle age often suffer from these alterations so that the possession of these animals could be useful. In order to describe some variables of psycho-emotional health (anxiety, depression, vulnerability to stress) in people with DM2 and the effects of tenure of dogs on aspects of personal satisfaction and the motivations for carrying out physical activities, a descriptive study was carried out. The work included 24 people with dogs and 24 without them, who were patients of the Diabetic Care Centre of Havana. No significant differences were found between middle-aged patients with DM2 with or without companion dogs in relation to indicators of psychic stability, but a trend of lower levels of anxiety was observed in those with companion dogs. Patients with companion dogs showed great personal satisfaction and perceived benefits in psycho-emotional health with respect to the motivations for carrying out physical activities due to the possession of the animal.